Art-identity founders, venturing processes, and entrepreneurship: Implications for policy. Issue 4 (2nd October 2021) - Casulli, Lucrezia; Knox, Stephen; MacLaren, Andrew C.; Farrington, Thomas
ABSTRACT: A growing body of literature in entrepreneurship argues that extant conceptualizations of the venture journey are not representative of the broad forms that entrepreneurship may take. This results in ill-informed policy that, in turn, feeds into support programs that work for ventures with certain profiles but are unsuitable for many other forms of enterprise. In this article, we seek to explore how this selective form of theorizing and related policy intervention plays out in art-identity ventures, being those that defy commercial priorities and pursue creative practice. We engage in this debate with a view to framing the status quo from the perspective of art-identity ventures, diagnosing the problems represented by this, and proposing some ways forward through which policy could resolve apparent tensions.